Differences in children's exposure to television advertising of unhealthy foods and beverages in Spain by socio-economic level - Miguel Ángel Royo-Bordonada; Cristina Cavero-Esponera; María Mar Romero-Fernández; Cristina González-Díaz; Elena Ordaz Castillo (BMC, 2024)
Abstract Background The influence of food advertising on food preferences and consumption could also contribute to the socio-economic inequalities among Spanish children in terms of eating habits and childhood obesity. Although the main food advertising channel targeted at children in Spain is television, available studies estimate exposure indirectly by combining content data with audience data. The aim of this study was therefore to describe the frequency of exposure to television advertising of unhealthy foods and drinks, measured directly, among Spanish children and adolescents, and analyse its socio-economic inequalities. Methods Observational study of television advertising impacts in a sample of 1590 children aged 4 to 16 years drawn from a consumer panel representative of the Spanish population in this age group, over the course of a full week of broadcasting in February 2022. The sample was obtained through stratified random sampling by Autonomous Region, with quotas being set by reference to socio-demographic variables. Exposure was measured with an audiometer, and the nutrient content of the food and drink advertised was analysed using the nutrient profile of the WHO Regional Office for Europe. We used the Chi-squared test to analyse possible differences in advertising coverage by socio-economic level. Results The participants saw a weekly mean of 82.4 food and drink commercials, 67.4 of which were for unhealthy products (81.8%), mostly outside the child-protection time slot. On average, low-social class participants received 94.4% more impacts from unhealthy food and drink advertising than did high-class participants (99.9 vs. 51.4 respectively). The mean advertising coverage of unhealthy foods and drinks was 71.6% higher in low-class than in high-class participants (10.9% vs. 18.7%; p = 0.01). Conclusion Spanish children and adolescents received an average of 10 impacts per day from television spots for unhealthy foods and drinks. The exposure of low-class children is double that of high-class children, a finding compatible with the high prevalence of childhood obesity in Spain and the related socio-economic inequalities. To protect Spanish minors from the harmful effects of food advertising and reduce the related social health inequalities would require the implementation of a 24:00 watershed for unhealthy food advertising on television.